1999
DOI: 10.1074/jbc.274.33.23328
|View full text |Cite
|
Sign up to set email alerts
|

The Acid-labile Subunit of the Serum Insulin-like Growth Factor-binding Protein Complexes

Abstract: The acid-labile subunit (ALS) is a glycosylated 85-kDa member of the leucine-rich repeat (LRR) protein superfamily and circulates in ternary complexes with the insulin-like growth factors (IGFs) and their binding proteins (IGFBPs). These complexes are thought to regulate the serum IGFs by restricting IGF movement out of the circulation. However, little is known about how ALS binds to IGFBP-3 or -5, which link the IGFs to ALS. To investigate potential sites of interaction, the ALS structure has been modeled wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…IGFBP-5 binds IGF-1 with an even higher af®nity than IGFBP-3, and may also form a IGF-1/IGFBP-5/ALS complex. 87,88 Practically all of the remaining IGF-1 is bound to the IGFBPs-1, -2, -4 and -6, which have lower IGF-1 binding af®nities, and do not form complexes with ALS. 77,85,86 Therefore, a decrease in plasma IGFBP-3, or a relative transfer of IGF-1 from the IGFBPs-3 or -5 to smaller the IGFBPs not complexed with ALS is believed to result in increased IGF-1 availability to its tissue receptors.…”
Section: Androgens the Androgen Hypothesismentioning
confidence: 99%
“…IGFBP-5 binds IGF-1 with an even higher af®nity than IGFBP-3, and may also form a IGF-1/IGFBP-5/ALS complex. 87,88 Practically all of the remaining IGF-1 is bound to the IGFBPs-1, -2, -4 and -6, which have lower IGF-1 binding af®nities, and do not form complexes with ALS. 77,85,86 Therefore, a decrease in plasma IGFBP-3, or a relative transfer of IGF-1 from the IGFBPs-3 or -5 to smaller the IGFBPs not complexed with ALS is believed to result in increased IGF-1 availability to its tissue receptors.…”
Section: Androgens the Androgen Hypothesismentioning
confidence: 99%
“…The 150 kDa complexes cannot cross the capillary endothelial barrier, which prolongs the half-life of IGFs, IGFBP-3 and IGFBP-5, in the circulation (9)(10)(11). This seems to play an important role in the regulation of the bioavailability of IGFs to the tissue compartments.…”
Section: Introductionmentioning
confidence: 99%
“…About 75% of the mature protein consists of the consensus motif for the LRR superfamily of proteins. These leucine-rich domains organize ALS into a doughnut-shaped structure (11,12). Whereas ALS readily binds to binary complexes of IGFs and IGFBP-3, it does not interact directly with free IGFs and shows only a very low affinity for unliganded IGFBP-3 (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the IGFs in serum are associated with the most abundant binding protein, IGFBP-3, which can combine with another protein, known as the acid-labile subunit or ALS, to form heterotrimeric complexes containing IGF, IGFBP-3 and ALS . ALS is a leucine-rich glycoprotein of approximately 85 kDa, the protein core of which is predicted to be largely toroidal (Leong et al 1992, Janosi et al 1999b). It has recently been shown that ALS can also form similar ternary complexes with IGFBP-5 and IGFs (Twigg & Baxter 1998), although IGFBP-5 complexes would be expected to be relatively minor carriers of IGFs compared with IGFBP-3, due to the 5-to 10-fold lower serum IGFBP-5 concentration (Baxter & Martin 1986, Mohan et al 1995.…”
Section: Introductionmentioning
confidence: 99%